MORALITAS ANAK DAN KAITANNYA DENGAN URGENSI PENDIDIKAN ISLAM - Syarifuddin Ondeng (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2007)
The morality issues always colored human life from the changing of time. The basic principle of morality is identically with character or ethics. These terms have similar meaning, those are; habit, character, and disposition. The morality always refers to good and bad aspect of someone, whether he is an adult or a child. In Islam, child’s morality does not only inform good aspect, but also bad aspect in his behavior. Thus, the important thing is how to show Islamic education toward the child. Therefore, he/she can apply goodness in his life, so that he gets benefit for himself. In spite of the consequence of child’s morality and the urgent of Islamic education is very interesting to be studied accurately and deeply.